Communication for forestry management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The Forestry Production and Development Operation (OAPF) project was launched in Mali with the task of ensuring participative and integrated management of three classified forests within a radius of 100 km around the capital, Bamako. The project...